Managerial Incentives, Risk Aversion, and Debt - Milidonis, Andreas; Stathopoulos, Konstantinos (Journal of Financial and Quantitative Analysis, 2014)
Abstract We investigate the risk choices of risk-averse CEOs. Following recent theoretical work, we expect CEO risk aversion to be more pronounced in firms with high leverage or high default probability. We find that the CEOs of these firms reduce firm risk, even in the presence of strong risk-taking incentives. Our results are robust to controls for the sensitivity of CEO wealth to stock price changes, firm risk determinants, the endogenous feedback effects of firm risk on CEO incentives, unobserved firm and market effects, and debt governance. The impact of CEO risk aversion is economically significant.